Influence of Workload and Work Stress on Motivation and Performance of Outpatient Nurses in Region C - Evangelia Yuninda; Medan Nababan (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study aims to determine and analyze the effect of workload and work stress on work motivation and performance of outpatient nurses in Health Services in Region C. The results of this study are expected to provide input for Health Service leaders and nursing managers in improving nurse performance which can have an impact on the quality of nursing care services. The research method used is descriptive and verification analysis. Data collection used is interviews using questionnaires accompanied by observation and literature techniques. Sampling using proportional random sampling. Data collection in the field was carried out in 2024 with a population of 170 people and a research sample of 119. The data analysis technique used Path Analysis. The results of the study showed that in general the workload, work stress, work motivation, and performance of nurses tend to be high and less good. There is an effect of workload and work stress on work motivation both partially and simultaneously and work motivation affects the performance of outpatient nurses in Health Services in Region C. There must be a balanced division of workload and equal responsibility among nurses.